The specific signs of lung ultrasound to diagnose pulmonary hemorrhage of the newborns: Evidence from a multicenter retrospective case-control study - Liu, Jing; Chi, Jing-Han; Lu, Zu-Lin; Fu, Wei (Frontiers in Pediatrics, 2023)
Objectives: Pulmonary hemorrhage (PH) is one kind of critical lung diseases in newborn infants, which is the most difficult one to be diagnosed by ultrasound. This study was to investigate the specific ultrasonic signs of PH in order to better diagnose neonatal PH by using lung ultrasound (LUS). Methods: A total 168 newborn infants were enrolled in this study, which included PH, pneumonia, meconium aspiration syndrome, and newborns without lung diseases, there were 42 cases in each group. In a quiet state, infants were placed in the supine, lateral or prone position for the examination. Each lung was divided into the anterior, lateral and posterior regions, then each region of both lungs was scanned with the probe perpendicular to the ribs or parallel to the Intercostal spaces. Results: The major results showed that: (1) the common LUS manifestation of PH includes lung consolidation, air bronchograms, fluid bronchograms, pleural effusion, shred signs, pleural line abnormality and B-lines，while fibrin deposition sign is a rare sign of PH. (2) Co-existing of lung consolidation with fluid bronchograms and pleural effusion is the specific sign of PH with a sensitivity of 81.0%, specificity of 98.4% and the positive predictive value (PPV) was 94.4%. (3) Fibrin deposition sign is an uncommon specific LUS sign of PH with a sensitivity 28.6%, specificity of 100% and the PPV was 100%. (4) Nine patients (21.4%) were diagnosed with PH based on ultrasound findings before oronasal bleeding. (5) The survival rate of infants with PH was 100% in this study. Conclusion: LUS is helpful for the early diagnosis of neonatal PH and may therefore improve the prognosis. The lung consolidation with fluid bronchograms and pleural effusion as well as fibrin deposition sign are specific to diagnose PH by using LUS.